The travelling athlete - Nikolic, N. (Triathlon Medicine, 2019)
Travel is an integral part of athletes` life and the triathlon season is organised as a national or international string of events that requires weekly or biweekly travel to matches. By the nature of their sport, the triathlon athletes` racing field environment can differ much from their home one and can have a decisive influence on the final success in the competition. Climate, epidemiological environment or medical support at the new destination can much differ during the season. Such a major environmental difference can strongly influence, not only athletes` fitness abilities, but also their health. Different modes or transport can also influence the physical and psychological well-being of the athlete. The purpose of this chapter is to highlight knowledge on travel sport medicine, formed in the series of recommendations that could be useful in protecting athletes` health abroad and therefore enhancing their competitive edge in triathlon events. Subjects include pre-competition/pretravel preparations, adaptation to new destination, nutrition, protection from the Sun and cold, rehydration, nutrition when travelling, problem of fatigue, diarrhoea treatment and prevention, personal protection and security precautions.